Prospects for Neutron Reactions on Excited States in High-Density Plasmas - Thompson, Ian J. (Frontiers in Physics, 2022)
With the reactions of high flux neutrons, such as in a DT plasma, there is a prospect of seeing new kinds of neutron-nucleus reactions for the first time. If neutrons excite a heavy nucleus, for example, there is possibility of a second neutron reacting on excited states of the residual nucleus before that nucleus has decayed to its ground state. The possibility of such reactions on excited states has rarely been considered. The cross section for neutron induced fission on the isomeric state of U has been measured and calculated , and reactions on rotationally excited nuclear states has been calculated . In high flux plasmas, however, a much wider range of reactions is possible. We therefore need to consider much higher-energy excited states than previously modeled, and whether second neutrons are likely to rescatter on those excited states. To determine the likelihood of such rescattering events, we first need to know the probable time series of nuclear decays of those excited states. The lifetimes of many low-lying states have been measured experimentally, but now we need to know the lifetimes of the many higher excited states that could be produced from incident 14 MeV neutrons. These are too numerous to be measured and also too numerous to be calculated individually, so statistical Hauser-Feshbach decay models are used. I show some lifetime calculations for Y, Xe, and Au targets, and predictions for the number of rescattering events in plausible plasma scenarios.